2013
DOI: 10.1371/journal.pone.0082247
|View full text |Cite
|
Sign up to set email alerts
|

Surgically Induced Interpregnancy Weight Loss and Prevalence of Overweight and Obesity in Offspring

Abstract: IntroductionAccording to the fetal overnutrition hypothesis, obesity in pregnancy predisposes the offspring to obesity. Previous studies have suggested that after biliopancreatic surgery for obesity, the offspring is less likely to be obese. This study aims to further compare the BMI development of children born before and after maternal surgical weight loss.MethodWomen with at least one child born before and one child born after bariatric surgery were identified by record-linkage. Information about maternal B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 40 publications
0
43
0
1
Order By: Relevance
“…8,46,47 Current evidence to advocate preconception weight loss in humans to decrease the risk of childhood obesity is mostly from association studies of surgically induced interpregnancy weight loss in mother and incidence of obesity in children. 4854 These studies reported that children delivered after surgery have lower risks of being overweight and obese than do their siblings born before surgery. Of note, these surgeries are also likely to alter patients' eating habits, and this effect may contribute to the improvement in the child’s overall health status in addition to maternal weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…8,46,47 Current evidence to advocate preconception weight loss in humans to decrease the risk of childhood obesity is mostly from association studies of surgically induced interpregnancy weight loss in mother and incidence of obesity in children. 4854 These studies reported that children delivered after surgery have lower risks of being overweight and obese than do their siblings born before surgery. Of note, these surgeries are also likely to alter patients' eating habits, and this effect may contribute to the improvement in the child’s overall health status in addition to maternal weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2013 study, Wahl et al analyzed a collection of large GWAS set with the 450k array in peripheral blood . The discovery set contained a mix of individuals of Southeast Asian ( n = 2,680) and European ( n = 2,707) ancestry and identified 278 BMI‐associated CpGs residing in 207 genetic loci while correcting for leukocyte cell‐type proportions.…”
Section: Ewas For Obesity (Bmi) In Peripheral Bloodmentioning
confidence: 99%
“…; Willmer et al . ). A recent systematic review highlighted the lack of good‐quality intervention studies assessing the effect of dietary‐induced weight loss prior to conception on health‐related variables in obese and overweight women and their offspring (Forsum et al .…”
Section: Impact Of Maternal Nutritional Status On Early Growthmentioning
confidence: 97%